TraK and TraB Are Conserved Outer Membrane Proteins of the Neisseria gonorrhoeae Type IV Secretion System and Are Expressed at Low Levels in Wild-Type Cells - Ramsey, Meghan E. (American Society for Microbiology, 2014)
Neisseria gonorrhoeae uses a type IV secretion system (T4SS) to secrete chromosomal DNA into the medium, and this DNA is effective in transforming other gonococci via natural transformation. In addition, the T4SS is important in the initial stages of biofilm development and mediates intracellular iron uptake in the absence of TonB. To better understand the mechanism of type IV secretion in N. gonorrhoeae, we examined the expression levels and localization of two predicted T4SS outer membrane proteins, TraK and TraB, in the wild-type strain as well as in overexpression strains and in a strain lacking all of the T4SS proteins. Despite very low sequence similarity to known homologues, TraB (VirB10 homolog) and TraK (VirB9 homolog) localized similarly to related proteins in other systems. Additionally, we found that TraV (a VirB7 homolog) interacts with TraK, as in other T4SSs. However, unlike in other systems, neither TraK nor TraB required the presence of other T4SS components for proper localization. Unlike other gonococcal T4SS proteins we have investigated, protein levels of the outer membrane proteins TraK and TraB were extremely low in wild-type cells and were undetectable by Western blotting unless overexpressed or tagged with a FLAG3 triple-epitope tag. Localization of TraK-FLAG3 in otherwise wild-type cells using immunogold electron microscopy of thin sections revealed a single gold particle on some cells. These results suggest that the gonococcal T4SS may be present in single copy per cell and that small amounts of T4SS proteins TraK and TraB are sufficient for DNA secretion.